Growth and optical properties of nanowires - Bose, P; Oudhia, A; Shukla, N (Recent Research in Science and Technology, 2012)
The present paper reviews the growth mechanism, processes and optical properties of nanowires with special reference to ZnO. A brief description of free standing vertical nanowires of ZnO grown in our lab is also included.